2018
DOI: 10.1093/pm/pny114
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Use Among Veterans of Recent Wars Receiving Veterans Affairs Chiropractic Care

Abstract: Nearly one-third of OEF/OIF/OND veterans receiving VA chiropractic services also received an opioid prescription, yet the frequency of opioid prescriptions was lower after the index chiropractic visit than before. Further study is warranted to assess the relationship between opioid use and chiropractic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…For example, although our data were insufficient to analyze for risk of opioid use, several recent studies have found that utilization of nonpharmacologic pain therapies leads to decreased opioid use. [17][18][19][20][21] Future research could explore the benefit of the PSC model in reducing overprescription of opioids. Additionally, we cannot be certain that variation in access to care was identical across the 3 sites; however, the 3 sites are part of the same health care system that strives for standardization, including monitoring a metric from time of patient call to time seen in clinic.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…For example, although our data were insufficient to analyze for risk of opioid use, several recent studies have found that utilization of nonpharmacologic pain therapies leads to decreased opioid use. [17][18][19][20][21] Future research could explore the benefit of the PSC model in reducing overprescription of opioids. Additionally, we cannot be certain that variation in access to care was identical across the 3 sites; however, the 3 sites are part of the same health care system that strives for standardization, including monitoring a metric from time of patient call to time seen in clinic.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 99%
“…For instance, opioid overuse/misuse has been frequently reported among individuals of low socioeconomic status and those with behavioural health problems. 36 37 Chronic pain is prevalent among these groups, [31][32][33][34][35][36][37][38][39] and a primary motivation of chronic pain sufferers for misusing opioids is to relieve physical pain. 37 Therefore, our regression analyses described below ('quantitative data analysis') will control for these variables.…”
Section: Aimmentioning
confidence: 99%
“…These variables have been shown to be associated with CNCP and opioid use. [31][32][33][34][35][36][37][38][39] In our analysis, we will explore variance inflation factors (VIFs) to assess collinearity between independent variables. If multicollinearity is detected between two or more variables (ie, VIFs ≥10), 49 then we will compare regression models, each separately containing one of the collinear variables, to one another and select the model containing the variable that produces the lowest Akaike information criterion.…”
Section: Quantitative Data Collectionmentioning
confidence: 99%
“…[5] The high prevalence of these pain conditions and the potential negative effects of prescription opioid use underscore the need to adhere to clinical practice guidelines -which recommend non-pharmacological therapies as frontline treatments --in the management of MSK conditions. [6,7] Prior work has shown a negative association between chiropractic use and opioid prescriptions among Veterans of recent wars [8] and other United States populations. [9] In 2016, VA Health Services Research and Development State-of-the-Art Conference on Non-Pharmacological Treatments for Chronic Pain recommended the increased uptake of evidence-based non-pharmacological approaches by VA facilities.…”
Section: Introductionmentioning
confidence: 99%